IMPLEMENTASI MANAJEMEN KINERJA FORUM KOMUNIKASI DINIYAH TAKMILIYAH (FKDT) KECAMATAN DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH DINIYAAH TAKMILIYAH AWALIYAH DI KECAMATAN CINGAMBUL KABUPATEN MAJALENGKA - Masduki, Masduki (STKIP Pesisir Selatan, 2023)
The background to this research was conducted to determine the extent of implementation performance management of the Diniyah Takmiliyah Communication Forum (FKDT) in improving the quality of Diniyah Takmiliyah Awwaliyah Madrasah Education in Cingambul District, Majalengka Regency. In conducting this research the author used a qualitative approach; Qualitative research is carried out to build knowledge through understanding and discovery. The qualitative research approach is a research and understanding process based on methods that investigate social phenomena and human problems. In this study, researchers observed, interviewed and searched for documents related to FKDT and MDTA both through FKDT administrators, madrasa heads and MDTA teachers. This is done to find research results that are in accordance with the problem formulation. Based on the research results, the following conclusions can be drawn; The implementation of Subdistrict FKDT performance management in improving the quality of MDTA education in Cingambul District has generally been carried out quite well, by utilizing the MDTA head, the FKDT program as well as MDTA teachers as a step in implementing FKDT performance management. Even though it is felt that it has not been optimal at the level of implementation, it requires a real program that is needed by the MDTA head and his teachers. Keywords: Performance Management, FKDT and MDTA.